Relationship between the “Don Bosco” educational model and school coexistence in an institution educational of Ancash - Oscco Calle, Yesmi Ivette (2023)
The research has as an objective to verify the relationship between the educational model from Don Bosco and the relations at school between the fourth graders of secondary from San Luis County, Ancash. The level of the investigation is descriptive, the type of investigation is substantive and the design is correlational. The population coincides with the sample, which was deliberately selected. In this sample, 25 fourth-year high school students participated. The instruments used to collect information on the variables correspond to a Likert scale and a survey. The results obtained confirm a significant relationship between the “Don Bosco” educational model and school coexistence. In conclusion, it was shown that the forming pillars of reason, religion and love develop and stabilize human relationships.